The quantum theory of light - Loudon, Rodney (Oxford New York Oxford University Press, 2000)
"The book is written as a textbook, with the treatment as a whole appropriate for graduate or postgraduate students, while earlier chapters are also suitable for final-year undergraduates. Over 100 problems help to reinforce the understanding of the material presented."--Jacket.
Introduction: The photon -- 1. Planck's radiation law and the Einstein coefficients -- 2. Quantum mechanics of the atom-radiation interaction -- 3. Classical theory of optical fluctuations and coherence -- 4. Quantization of the radiation field -- 5. Single-mode quantum optics -- 6. Multimode and continuous-mode quantum optics -- 7. Optical generation, attenuation and amplification -- 8. Resonance fluorescence and light scattering -- 9. Nonlinear quantum optics.
Includes bibliographical references and index.
Keywords: Quantum optics; Optique quantique